The Effect of Progressive Muscle Relaxation on Sleep Quality and Anxiety Level of Students Confirmed Covid-19 - Titin Supriatin; Yani Trihandayani; Yani Nurhayani; Pratuma Rithpho (International Journal of Nursing Information, 2022)
Coronavirus disease is a virus that causes respiratory system disorders. Based on data from the Indonesian Ministry of Health, 2022, the number of covid-19 exposures that have been confirmed positive is 6,512,913, recovered as 6,319,990 died 158,768. Progressive muscle relaxation focuses on muscle activity. The purpose of this exercise is to lower the tension. This study aims to measure the effectiveness of exercise on sleep quality and anxiety levels. This study is a quantitative research method, using purposive samples with a quasi-experimental study pretest-posttest one-group research design. This study sampled 24 students who declared confirmed Covid-19. The value of sleep quality is 2.17, with a standard deviation of 0.761. The results obtained a p-value of 0.000, then the p < α where H0 was rejected, significant influence on sleep quality before and after exercise. The value of the level of anxiety after exercise is 2.17, with a standard deviation of 0.381. The results p-value of 0.000, then the p < α where H0 was rejected, significantly influenced the level of student anxiety before and after exercise. The contribution of this research can be used for nursing information, especially for patients who are confirmed Covid-19.